Patients with Multiple Functional Gastrointestinal Disorders (FGIDs) Show Increased Illness Severity: A Cross-Sectional Study in a Tertiary Care FGID Specialty Clinic - Sabrina Berens; Felicitas Engel; Annika Gauss; Jonas Tesarz; Wolfgang Herzog; Beate Niesler; Esther Stroe-Kunold; Rainer Schaefert (Gastroenterology Research and Practice)
Objectives. Overlaps between different functional gastrointestinal disorders (FGIDs) are common. However, little is known about the impact of this overlap on patients’ health status. This study is aimed at analyzing the differences between patients with multiple as compared to one single FGID. Methods. A retrospective, cross-sectional study was conducted with patients presenting to a tertiary care FGID specialty clinic between 06/2012 and 01/2015 (n=294). They were characterized primarily according to their GI symptom severity (IBS-SSS) and secondarily to their physical as well as psychosocial symptom burden, quality of life, health care utilization, and work-related impairment. Differences between patients with >1 vs. 1 FGID were analyzed. Results. Of the 294 patients, 92.2% fulfilled the Rome III criteria for any FGID, and 48.0% had >1 FGIDs. FGID patients had a median age of 38 [23.0] years; 72.0% were female. Median GI symptom severity (IBS-SSS) scores were 339 [126] and 232 [163] in patients with >1 and 1 FGID, respectively (p<.001). Furthermore, patients with >1 FGIDs had higher general somatic symptom severity, higher illness anxiety, lower quality of life, and more work-related impairment. Almost no differences were found regarding their somatic as well as mental comorbidities. Conclusions. Multiple FGIDs are associated with an increased risk for complicated courses of illness as reflected in higher GI and somatic symptom severity, as well as stronger psychosocial and diet- and work-related impairment. Stepped and interdisciplinary models of care including psychosocial expertise and dietary advice are needed, especially for patients with multiple FGIDs.